Perencanaan Tebal Perkerasan Lentur Ruas Jalan Teluk Bayur-Kota Padang Sta 0+000-5+000 - Rifwan, Fitra; Oktaviani, Oktaviani; Sari, Nadra Mutiara; Kurniati, Yuni (Jurnal Pembangunan Nagari; Vol 3 No 2 (2018), 2018)
The Padang city is going to change the land use because of a transportation development. The increasing number of vehicle that occure every years  in this city make a problem related to the  capacity of the transportation  infrastructure, such as the road. The road of Teluk Bayur - Padang  is its location which  is the area of case study. The municipal and provincial authority  are working together to solve  the problem with conducting the road  improvement project. It is worked by using 2 road types, such as rigid and flexible pavement. The different types become a little question  why  they are not the same in equal  traffic load based on LHR data. According to the conditions, an alternative design needs to be made.  The design is not different  with existing traffic  load conditions and has durability for 10 years. The design is flexible pavement  analyzed by using the guideline ‘Petunjuk Perencanaan Tebal Perkerasan Lentur Jalan Raya dengan Metode Analisa Komponen (MAK)’ , 1987  made by Ministry of Public Works of Indonesia. The results produced each layer's thickness of the road, such as D1 = surface = 8 cm, D2 = subbase = 24 cm, and base = 10 cm.